Finite element analysis of the thermomechanical behavior of metal matrix composites (MMC) - Zaoui Bouchra; Baghdadi Mohammed; Boualem Serier; Mohammed Belhouari (Fracture and Structural Integrity)
In this work the finite element method (FEM) was used to analyze the mechanical behavior of the composite materials subjected to the mechanical loading. This behavior is studied in terms of stress intensity factor variation as a function of the applied stress intensity. The residual stresses induced in the composites, during the elaboration of these composites are taken into consideration in this study. The superimposition of these types of stresses (residuals and commissioning) is simulated here by thermomechanical stresses. The results obtained show that in the vicinity very close to the fiber-matrix interface and under the effect of this loading type, the matrix cracks propagate in modes I, II and III, and far from the interface, in mode I. The propagation kinetics is slowed down by the interface-crack interaction.